Platelet‐rich plasma intra‐articular knee injections from open preparation techniques do not pose a higher risk of joint infection: A systematic review of 91 randomized controlled trials and 5914 injections - Mohammad Sami Alazzeh (19730056) (2024)
Purpose To compare the infection rate of intraarticular platelet‐rich plasma (PRP) knee injections between open and closed techniques in randomized controlled trials (RCTs) published in the last decade. Methods Following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines, PubMed, Scopus and Virtual Health Library were accessed in October 2022 using the terms ‘platelet‐rich plasma’, ‘PRP’, ‘knee’ and ‘tibiofemoral’ alone and in combination with Boolean operators AND/OR. RCTs published during the last 10 years evaluating PRP intra‐articular knee injections were considered eligible. Studies were excluded if the kit/preparation technique was not described. Data were presented using individual studies' absolute values, totals, and pooled percentages. Publication bias was assessed using the ROBIS tool. Results Ninety‐one studies met the predetermined eligibility criteria. Forty‐one implemented a closed technique, while 50 were open. All studies implementing a closed technique disclosed their commercial kits. Only 16 studies (17.58%) failed to report joint infections. Among the studies reporting joint infections as outcomes, 30 implemented a closed technique with 1195 patients, 1921 intra‐articular knee injections and 95.44% of patient follow‐up. On the other hand, 45 of them implemented an open technique with 2290 patients, 3993 intra‐articular knee injections and 97.07% of patient follow‐up. No patient had a joint infection among the included studies. Thirty‐three studies prepared their PRP in controlled environments (36.26%). Most studies did not report where the preparation occurred (48.35%). Only twelve studies disclosed using laminar flow during preparation (13.19%). The infection rate for both techniques was 0 per 1000 knee injections. Conclusion Open PRP preparation techniques do not pose a higher risk of joint infection and can lower manufacturing costs when appropriate facilities are available. However, PRP preparation setting and laminar flow implementation data are deficient, and minimal requirements for good manufacturing practices demand further studies while adhering to local and regional regulations. Level of Evidence Level I, systematic review of RCTs. Other Information Published in: Journal of Experimental Orthopaedics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/jeo2.70002